2003
DOI: 10.1091/mbc.e02-11-0711
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of a Golgi Complex Lysophospholipid Acyltransferase Induces Membrane Tubule Formation and Retrograde Trafficking

Abstract: Recent studies have suggested that formation of Golgi membrane tubules involves the generation of membrane-associated lysophospholipids by a cytoplasmic Ca2+-independent phospholipase A2 (PLA2). Herein, we provide additional support for this idea by showing that inhibition of lysophospholipid reacylation by a novel Golgi-associated lysophosphatidylcholine acyltransferase (LPAT) induces the rapid tubulation of Golgi membranes, leading in their retrograde movement to the endoplasmic reticulum. Inhibition of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 55 publications
5
54
1
Order By: Relevance
“…Previous studies have provided evidence that membrane tubule formation from the Golgi complex and endosomes requires the generation of curve-inducing LPLs by the direct action of a cytoplasmic Ca 2ϩ -independent PLA 2 enzyme on membrane phospholipids (de Figueiredo et al, 1998Polizotto et al, 1999;Drecktrah et al, 2003). Here we provide evidence for a previously unsuspected role for heterotrimeric G-proteins in the regulation of PLA 2 -mediated membrane tubule formation.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous studies have provided evidence that membrane tubule formation from the Golgi complex and endosomes requires the generation of curve-inducing LPLs by the direct action of a cytoplasmic Ca 2ϩ -independent PLA 2 enzyme on membrane phospholipids (de Figueiredo et al, 1998Polizotto et al, 1999;Drecktrah et al, 2003). Here we provide evidence for a previously unsuspected role for heterotrimeric G-proteins in the regulation of PLA 2 -mediated membrane tubule formation.…”
Section: Discussionsupporting
confidence: 59%
“…In particular, LPLs on the cytoplasmic surfaces of organelle membranes could contribute to the generation of outward bending, thus initiating tubule formation (Burger, 2000;Huijbregts et al, 2000;Huttner and Schmidt, 2002;Brown et al, 2003). Support for this idea was provided by studies showing that inhibition of LPL reacylation by a Golgi-associated lysophospholipid acyltransferase (LPAT) also leads to increased tubule formation and retrograde trafficking (Drecktrah et al, 2003). These studies suggest that LPATs function to negatively influence membrane tubulation by limiting the accumulation of LPLs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their inverted cone shape LysoPLs influence membrane curvature and, consequently, also the formation and fission of vesicles (36,37). It was shown that increasing the ratio of LysoPL/PL in the outer leaflet of a membrane causes an outward curvature that at its most extreme leads to tubule formation (37). Phospholipases A 2, which generate LysoPLs, play critical roles in multiple membrane trafficking events.…”
Section: Discussionmentioning
confidence: 99%
“…by coats) may induce large-scale sorting by specifically including the unsaturated lipids in the forming bud. In this way, highly curved retrograde tubules [20] could also release unsaturated lipids from the Golgi. Whether a similar sorting reaction occurs on the cytosolic surface, excluding the cytosolically oriented phosphatidylserine from the retrograde pathway, remains to be determined, as the lipid organization on the cytosolic side of lumenal sphingolipid-cholesterol domains is unknown.…”
Section: Sphingolipid/cholesterol Domains and Sortingmentioning
confidence: 99%
“…Lipid transport between ER and Golgi. A bidirectional vesicular transport pathway connects the ER and Golgi, although tubulation is also observed [20]. Cholesterol spontaneously exchanges between membranes.…”
Section: Sphingolipid/cholesterol Domains and Sortingmentioning
confidence: 99%